1990
DOI: 10.1039/p19900003129
|View full text |Cite
|
Sign up to set email alerts
|

Latent inhibitors. Part 6. Inhibition of dihydro-orotate dehydrogenase by substituted 5-benzylhydantoins

Abstract: A series of substituted 5benzyl-3-(1 -carboxy-2-phenylethyl) hydantoins was prepared by condensation of aromatic aldehydes with the corresponding 5-unsubstituted hydantoin followed by reduction of the intermediate benzylidene derivative. The compounds were assessed as inhibitors of dihydroorotate dehydrogenase from Clostridium oroticum. It was found that hydrophobic and electron-donating substituents in the phenyl ring of the benzyl group favoured binding and irreversible inhibition. The results for the series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…1,3−5 They have been notably presented as inhibitors of dihydro-orotate dehydrogenase from Clostridium (Zymobacterium) oroticum for the potential treatment of parasitic diseases. 6,7 From the synthetic point of view, these structures have been often reported as byproducts in peptide synthesis. 8−11 However, their structural and biological interests have given rise to the development of several methodologies for their preparation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3−5 They have been notably presented as inhibitors of dihydro-orotate dehydrogenase from Clostridium (Zymobacterium) oroticum for the potential treatment of parasitic diseases. 6,7 From the synthetic point of view, these structures have been often reported as byproducts in peptide synthesis. 8−11 However, their structural and biological interests have given rise to the development of several methodologies for their preparation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The hydantoin core offers numerous possibilities of substitutions, allowing building a large diversity of potential structures. In particular, 5-substituted-3-(alkoxycarbonyl)­alkyl-hydantoin derivatives (Figure ) present a particular substitution pattern, which make them interesting peptidomimetics and bioactive compounds with antiepileptic, anticonvulsant, antiarrhythmic, or antibacterial properties. , They have been notably presented as inhibitors of dihydro-orotate dehydrogenase from Clostridium ( Zymobacterium ) oroticum for the potential treatment of parasitic diseases. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of 18 are given in Table I. Howie et al (1990) reported an efficient method for the preparation of 18, but we could not compare it with our method because the yields were absent. [44][45][46][47].…”
Section: -(Arylmethylene)-2-thiohydantoins (20-27): Generalmentioning
confidence: 99%